2006
DOI: 10.1128/aem.03078-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Freeze-Dried Kefir Coculture as Starter in Feta-Type Cheese Production

Abstract: The use of freeze-dried kefir coculture as a starter in the production of feta-type cheese was investigated. Maturation of the produced cheese at 4°C was monitored for up to 70 days, and the effects of the starter culture, the salting method, and the ripening process on quality characteristics were studied. The use of kefir coculture as a starter led to increased lactic acid concentrations and decreased pH values in the final product associated with significantly higher conversion rates compared to salted renn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 67 publications
2
47
0
7
Order By: Relevance
“…Hence, it is not unreasonable to suggest the development of a microbial association, due to L. casei ATCC 393 cells, leading to repression of facultative pathogens, although pathogenesis has not been considered for all strains of the above microbial species. Suppression of staphylococci growth has been described in various food products by mixed LAB cultures [Dimitrellou et al, 2009;Kourkoutas et al, 2006b], while reduction of pathogenic bacteria counts in feces [de Waard et al, 2002;O'Mahony et al, 2001] and intestines of rats [de Waard et al, 2002;Liong et al, 2006;Montesi et al, 2005], due to the action of LAB and bifidobacteria has been previously reported. Further research using deliberately spiked animals with pathogens will give more insight into the role of L. casei ATCC 393 as endogenous protecting shield.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is not unreasonable to suggest the development of a microbial association, due to L. casei ATCC 393 cells, leading to repression of facultative pathogens, although pathogenesis has not been considered for all strains of the above microbial species. Suppression of staphylococci growth has been described in various food products by mixed LAB cultures [Dimitrellou et al, 2009;Kourkoutas et al, 2006b], while reduction of pathogenic bacteria counts in feces [de Waard et al, 2002;O'Mahony et al, 2001] and intestines of rats [de Waard et al, 2002;Liong et al, 2006;Montesi et al, 2005], due to the action of LAB and bifidobacteria has been previously reported. Further research using deliberately spiked animals with pathogens will give more insight into the role of L. casei ATCC 393 as endogenous protecting shield.…”
Section: Discussionmentioning
confidence: 99%
“…The microflora of kefir grains is remarkably stable, retaining activity for years if preserved and incubated under appropriate cultural and physiological conditions (1). Successful results have been achieved in studies where kefir was used as a starter culture for production of white pickled cheese (2), hard-type cheese (3), and Feta-type cheese (4).…”
Section: Introductionmentioning
confidence: 93%
“…Kovat's retention indexes were determined from the injection of a standard mixture containing the homologous series of normal alkanes (C 8 -C 22 ) in pure hexane under exactly the same experimental conditions as described above. Quantification of volatile compounds was carried out as described recently (Mallouchos et al, 2003;Kourkoutas et al, 2006) with some modifications. Specifically, methyl octanoate (Sigma-Aldrich, Poole, UK) diluted in pure hexane (Sigma-Aldrich) was used as an internal standard (IS) at various concentrations (0.88, 8.75, 87.5, and 875 µg/kg).…”
Section: Introductionmentioning
confidence: 99%